Edukasi Pola Makan Sehat: Kurangi Konsumsi Makanan Cepat Saji Untuk Hidup Lebih Sehat - Effendy, Devi Savitri; Muchtar, Febriana; Bahar, Hartati; Tossepu, Ramadhan; Namrin, Najwa; Aremanita, Nazhifa Nahda; Ainun, Nur Hikmah; Apriyani, Desi; Effendy, Lisnawati; Zamzam, Zamzam; Kalisi, Hadi (Pakis Journal Institute, 2024)
The program